Mediating role of gratification on the relationship between expectation and continuance intention to watch movies on YouTube - Abu Bakar, Mohd Syuhaidi (2017)
Various movies that were recently released in Malaysia were disappointing in ticket sales, however the number of users watching movies on YouTube have recorded an increase. The general objective of this study was to determine the potential of YouTube to substitute physical cinema as the new movie watching-platform among moviegoers in Malaysia. Specifically, the study aims to identify the relationships between expectations, gratification, and continuance intention to watch movies on the User-Generated Content (UGC) site. An online questionnaire using Google Forms were distributed to 400 YouTube users in Malaysia, selected through purposive sampling techniques. The variables and items were extracted from reviews of literature and were checked for convergent and discriminant validity using Confirmatory Factor Analysis (CFA). Structural Equation Modelling (SEM) under AMOS software was used in the analysis. Results of the SEM indicated that YouTube users in Malaysia were gratified with the social and the technological opportunities provided by YouTube. However, these users were not gratified with the movie selections on YouTube and have claimed that they were not gratified with the actual experience of watching movies on YouTube. Nevertheless, findings from this study have recorded a good chance for YouTube to substitute physical cinema in Malaysia, provided that Google were to develop a better synergetic content selection of movies and provide better actual experience for its stakeholders.